The effect of the number of hepatic inflow occlusion times on the prognosis of ruptured hepatocellular carcinoma patients after hepatectomy - Feng Xia; Zhiyuan Huang; Elijah Ndhlovu; Mingyu Zhang; Xiaoping Chen; Bixiang Zhang; Peng Zhu (BMC Surgery, 2022)
Abstract Background and aim It has been previously reported that inflow occlusion does not affect postoperative outcomes in hepatocellular carcinoma patients. However, for patients with ruptured hepatocellular carcinoma(rHCC), the effect of hepatic inflow occlusion and the number of occlusion times on the prognosis is unknown. Methods 203 patients with ruptured hepatocellular carcinoma were enrolled in this study. They were first divided into the non-hepatic inflow occlusion (non-HIO) group and the hepatic inflow occlusion (HIO) group. The Kaplan–Meier method was used to compare the recurrence-free survival and overall survival between the two groups. Patients in the HIO group were further divided into one-time HIO and two times HIO groups. KM method was also used to compare the two groups. Finally, independent risk factors affecting RFS and OS were determined by multivariate Cox regression analysis. Result In the non-HIO group, 1-,3- and 5-year OS rates were 67.0%, 41.0%, and 22.0%respectively, and RFS rates were 45.0%, 31.0%, and 20.0% respectively; In the one-HIO group, the 1-,3-, and 5-year OS rates were 55.1%, 32.1%, and 19.2% respectively, and RFS rates were 33.3%, 16.7%, and 7.7% respectively; In the two-HIO group, 1-,3-, and 5-year OS rates were 24.0%, 0.0%, and 0.0% respectively, and RFS rates were 8.0%, 0.0%, and 0.0% respectively. By Cox regression analysis, HIO was an independent risk factor for a poor prognosis in rHCC patients. Conclusion One time hepatic inflow occlusion did not affect postoperative OS, but negatively affected the RFS of rHCC patients; two times hepatic inflow occlusion negatively affected the postoperative OS and RFS in patients with rHCC.